Penalty for late payment of bank installments (Salam International Academic Journal, 2020)
Banking today is one of the most pressing needs of our age, and as ‎human relations fluctuate day to day, so there is a pressing need to ‎execute business relationships and transactions in every corner of the ‎world and what these banking relationships are? And how much is there ‎limits for Muslims and what will be the amount of interaction and delay ‎in the event of delay or failure? These are the questions we are looking ‎for.‎In the rabbi system, if the payment of debt is delayed, the amount of ‎profit is increased and due to the fear of underestimation of the ‎excessive profits caused by the delay in paying the debt (instalments of ‎debt) at the appointed time (due date). But participation and misery ‎are misused by people because of the lack of a “late payment damages” ‎law and delay payment of debt. So what is the way to block this abuse ‎and solving it in Islamic banking? ‎The significance of this research is that it is often thought that there is ‎no national or foreign language work in this case. Arabic is also widely ‎dispersed. Secondly, these concepts are from the ummah and are a ‎matter for the people. ‎The purpose of this study was to investigate how penalties are delayed, ‎and to understand how banks interact with this issue.‎In this research we have used typical library-specific methods and have ‎divided the discussion into two themes, followed by conclusions and ‎disputes, which provide the reader with an effective understanding of ‎the planned subject. ‎The results of the research show that our country’s laws are not serious ‎about delayed penalties and delayed payment of instalments. And the ‎lack of a proper jurisprudence resources, which cannot guarantee the ‎viability of the Islamic banking business with the performance ‎guarantee.‎